REACTION OF IBA-1-POSITIVE MICROGLIA CELLS IN THE SENSORIMOTOR CORTEX OF RATS WITH INDUCTION OF TRANSIENT ISCHEMIA - Yaremenko, L.M.; Вidna, L.P.; Shepelev, S.Ye.; Grabovyi, O.M. (World of Medicine and Biology, 2018)
In order to study the peculiarities of the reaction of iba-1-positive microglia cells in the cortex of rats with induction of transient ischemia against the background of previous sensitization by the brain antigen and the resulting changes, an experiment was carried out on 135 white mature male rats weighing 260-290 grams histological, immunohistochemical, morphometric and statistical methods of investigation have been applied. It has been established that sensitization by brain antigen leads to neurodegenerative changes in the cerebral cortex and, after a period of insignificant decrease, to an increase in the number of Iba-1 + -microglia cells and their hypertrophy, which can be treated as a neuroinflammation. Sensitization by brain antigen potentiates the reaction (increase in the specific amount) of microglia to a transient circulatory disturbance. Immunomodulator imunofan reduces the reaction of Iba-1 + -microglia in the recovery period after transient ischemia. This correlates with a more favorable course of the post ischemic process as a whole. The latter can be considered as a manifestation of the neuroprotective properties of imunophane.
Keywords: brain; sensitization; ischemia; Iba-1; microglia; imunophane